2006
DOI: 10.1016/j.jconrel.2006.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Uptake studies in rat Peyer's patches, cytotoxicity and release studies of alginate coated chitosan nanoparticles for mucosal vaccination

Abstract: The design of particulate vaccine delivery systems, particularly for mucosal surfaces, has been a focus of interest in recent years. In this context, we have previously described the development and the characterization of a new nanosized delivery system, consisting of a model antigen adsorbed to chitosan particles and coated with sodium alginate. In the present work the ovalbumin release profiles from these coated nanoparticles in different pH buffers were investigated and compared to those of the uncoated pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 49 publications
4
110
0
Order By: Relevance
“…The findings of the present work correlate with results of another study which indicate that both alginate-coated and uncoated chitosan microparticles did not induce spleen cell death [15]. However, a recent study showed that CaCl 2 -crosslinked alginate microparticles caused a slight reduction in cell viability in human umbilical vein endothelial cells (HUVEC) cells except supersaturated particle concentrations were employed [16].…”
Section: Cytotoxicity Of Microparticlessupporting
confidence: 87%
See 1 more Smart Citation
“…The findings of the present work correlate with results of another study which indicate that both alginate-coated and uncoated chitosan microparticles did not induce spleen cell death [15]. However, a recent study showed that CaCl 2 -crosslinked alginate microparticles caused a slight reduction in cell viability in human umbilical vein endothelial cells (HUVEC) cells except supersaturated particle concentrations were employed [16].…”
Section: Cytotoxicity Of Microparticlessupporting
confidence: 87%
“…Therefore, when phosphate is present in the dissolution medium used, probable destabilizing of calcium-crosslinked alginate matrix by phosphate ions has to be taken into account as it may cause a faster opening or breakdown of crosslinking than in 0.1M HCl medium (pH 1.2) where such a phenomenon does not occur. Loss of calcium ions from the alginate coating resulted in increase of the permeability of the coating and consequently, increased diffusion of the allergen into the release medium [15].…”
Section: Allergen Releasementioning
confidence: 99%
“…One of the reasons pointed as the basis of this decision is the fact that nanoparticle uptake by intestinal cells has been reported several times, either by the M-cells located in the Peyer's patches (Borges et al, 2006, Pinto Reis et , 2006) or by the enterocytes, benefiting from transcellular and paracellular transport (Cai et al, 2010, Pinto Reis et al, 2006. A first study revealed that, after oral delivery to mice of alginate nanoparticles containing the three drugs mentioned above plus etambutol, plasma drug levels were detected during 7-13 days.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…The preparation of chitosan-based hydrophilic nanogels has been widely described in the literature, employing penta sodium triphosphate (PSTP) as the complexing anionic molecule for the polycation chitosan [19][20][21][22][23][24][25]. Chitosan-based nanogels have been studied as carriers of oligonucleotides in gene therapy, for mucosal vaccination, in tissue engineering or drug delivery [26][27][28]. However, highly positive nanoparticles are generally cytotoxic, or are unselectively taken up by cells due to their positive charge, suggesting that developing negative chitosan-based nanogels could be of biological interest.…”
Section: Introductionmentioning
confidence: 99%
“…However, highly positive nanoparticles are generally cytotoxic, or are unselectively taken up by cells due to their positive charge, suggesting that developing negative chitosan-based nanogels could be of biological interest. Nanogels based on a chitosan core matrix decorated on their surface with polyanions have been described [28,29].…”
Section: Introductionmentioning
confidence: 99%